Study on the Creep Damage Characteristics of Shale under the Combined Action of Osmotic Pressure and Disturbance Load. (20th November 2021) - Wang, Junguang; Yu, Qingrong; Liang, Bing; Xuan, Zhangqing
Abstract : In the in situ modified fluidized mining engineering, the surrounding rock of the shaft wall is prone to creep instability damage under the action of disturbance and seepage water pressure, which seriously affects the stability of the surrounding rock of the deep in situ modified fluidized mining. In order to study the nonlinear creep damage and fracture characteristics of deep rocks under the combined action of seepage water pressure and disturbance load, a self-developed rock perturbation creep test rig under the action of seepage water pressure was used, and shale was used as the rock sample. In the method of staged loading, the rock uniaxial compression perturbation creep test under static axial pressure, different perturbation frequencies, and different seepage water pressures was carried out, and the creep characteristics of shale under the combined action of perturbation and seepage were studied. The results show that with the increase of seepage water pressure, the creep failure time of the rock decreases, and the ultimate strain value increases; with the increase of the disturbance frequency, the creep failure mode of the rock gradually transitions from shear failure to tension failure. When water pressure and disturbance load exist at the same time, rock creep is more sensitive to seepage water pressure; based on experimental results, a shale perturbation creep damage model considering the influence of seepage water pressure and disturbance frequency is established, and the model is verified. The research results have important theoretical significance for guiding the wellbore stability control of in situ modified fluidized mining engineering.